РІЗНІ ПІДХОДИ У ВИЗНАЧЕННІ СУТІ ТА ЗМІСТУ ПОНЯТТЯ "НАЦІОНАЛЬНА САМОСВІДОМІСТЬ МАЙБУТНІХ УЧИТЕЛІВ" (Педагогіка вищої та середньої школи, 2022)
The article deals with the problem o f formation o f national self-consciousness of a future teacher. The essence of the notion “national self-consciousness of a future teacher” and its structure have been revealedThe determinants offormation o f national self-consciousness o f a future teacher have been ascertained.